3D Helical Micromixer Fabricated by Micro Lost‐Wax Casting. Issue 1 (20th November 2019) - Tachibana, Daiki; Matsubara, Ken; Matsuda, Ryosuke; Furukawa, Taichi; Maruo, Shoji; Tanaka, Yoshimi; Fuchiwaki, Ohmi; Ota, Hiroki
Abstract: Micromixers produced by micro fabrication techniques have attracted attention for micro total analysis systems and lab‐on‐a‐chip applications in point‐of‐care testing. However, the fabrication and setup of micromixers have become more complex and more difficult. Considering the practical use of micromixers in medical and industrial applications, their designs can be simplified while maintaining high mixing efficiency. Rapid prototyping, represented by 3D printing having micro‐scale resolutions, is one promising technology to replace conventional fabrication methods such as soft lithography. Here, a 3D helical micromixer fabricated by micro‐scale lost‐wax casting is reported. The molds for lost‐wax casting are fabricated by fine 3D printing of a hard wax resin which can be removed from a polydimethylsiloxane block just by heating and washing with water, and a fine and smooth structure is realized. The optimized helical micromixer fabricated by lost‐wax casting promotes mixing efficiency compared with other micromixers. In addition, a monolithic microchannel having the helical 3D bridge structure is presented in this study. The demonstration is an important advancement toward the industrial applications of micromixers fabricated by micro‐scale 3D printing. The ability to fabricate complex structures can simply lead to the creation of more sophisticated mixers in the future. Abstract : A micromixer using a 3D helical channel is fabricated by the lost‐wax casting with molds made by 3D‐printing technology. The helical structure of the channel promotes the mixing of two fluids. It can be expected that microfluidic devices with more detailed structures can be created by using this method.